(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article discusses the role of ichthyophages, that is, fish-eating birds, in the biocenosis, and bioecological features. Information is presented on fish-eating birds found in fish farms in the Bukhara region, characteristics of encounters in reservoirs, periods of migration, and nesting ecology of nesting species.